(untitled) (Eurasian Journal of Media and Communications, 2021)
Early detection of violations of the formation of reproductive function in adolescent girls is an important problem in modern gynecology. Taking into account the frequency of hyperandrogenic conditions inherent in the pubertal period (according to different authors, from 25 to 30%), as well as the high frequency of the formation of various disorders of the reproductive system in this category of patients, it is necessary to search for pathological links in the endocrine system that can determine the development of the entire the range of functional and morphological changes.